Contemporary Approaches to Qualitative Research: Andragogical Strategies for Teaching and Learning - Tiffany T. Young; Wayne A. Babchuk (Adult Education Research Conference, 2019)
This inquiry provides practical guidelines for teaching and learning qualitative research methodology in adult education. Step-by-step procedures are clearly articulated for novice researchers and those new to qualitative research.
Keywords: Qualitative Research; Qualitative Methods